DIAGNOSTIC OF C-REACTIVE PROTEIN IN FEBRILE CHILDREN - Johanis Johanis; Aryati Aryati; Dominicus Husada; Djoko Marsudi; M. Y. Probohoesodo (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2012)
The measurement of C-reactive protein (CRP), an acute-phase protein synthesized by hepatocytes, is valuable to distinguish bacterialinfection from non-bacterial infections in children. The aim of this study is to know the diagnostic properties of quantitative CRPassociated with clinically bacterial and non-bacterial infection in febrile children. Febrile children which was studied were presentingin the Paediatric Emergency Department, their ages were up to 12 years, with axillary’s temperature ≥38.5° C, and the clinicallyundetectable source of fever were enrolled in this consecutive study from September, 2009, up to August, 2010. Informed consent wasobtained for the use of CRP evaluation. The CRP concentration was measured with immunoturbidimetry method (Pure auto S CRP latex(SS-type), Sekisui Medical Co., Ltd) and an auto photometer TMS 1024i. The main outcome result was the presence of the laboratoryexamination results, blood culture, or radio graphically. The receiver operator characteristic (ROC) curve was modelled for quantitativeCRP to identify the optimal test value. Eighty-six patients were enrolled in this study. Forty-one (47.6%) had bacterial infection and 45(52.3%) had non-bacterial infection. The CRP concentration was significantly different between the two groups (p=0.003). The ROCanalysis demonstrated an area under curve (AUC) 0.689, standard error (SE) 0.059, and 95% confidence interval (CI): 0.573-0.805.The optimal cut-off point for CRP in this data set at 5 mg/L, achieved sensitivity of 0.61, specificity of 0.71, and likelihood ratio 2.11(Kappa 0.003, McNemar 0.711) for the detection of bacterial infection in this population. The Quantitative CRP concentration is avaluable laboratory test for the evaluation of febrile children who are at risk of bacterial infection.